2010
DOI: 10.1002/cjce.20301
|View full text |Cite
|
Sign up to set email alerts
|

Destabilisation of homogeneous bubbly flow in an annular gap bubble column

Abstract: Experimental results are presented to show that there are very significant differences in the mean gas void fractions measured in an open tube and a annular gap bubble column, when operated at the same gas superficial velocity, using a porous sparger. Measurements were carried out in a vertical 0.102 m internal diameter column, with a range of concentric inner tubes to form an annular gap, giving diameter ratios from 0.25 to 0.69; gas superficial velocities in the range 0.014–0.200 m/s were investigated. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
5
19
2
Order By: Relevance
“…The sparger used in this study has "large" holes (d 0 41 mm), and the shape of the holdup curve is the one typically obtained for a sparger with similar hole openings (i.e., single/multiple nozzles, spider sparger or perforated plate sparger with a hole diameter greater than 1 mm); as expected, no peak can be observed in the holdup curve. Alternatively, when using "fine" spargers, a peak in the holdup curve may appear, as obtained by Al-Oufi (Al-Oufi et al, 2010, 2011, Schumpe and Grund (1986), and Zahradnik et al (1997).…”
Section: Bubble Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The sparger used in this study has "large" holes (d 0 41 mm), and the shape of the holdup curve is the one typically obtained for a sparger with similar hole openings (i.e., single/multiple nozzles, spider sparger or perforated plate sparger with a hole diameter greater than 1 mm); as expected, no peak can be observed in the holdup curve. Alternatively, when using "fine" spargers, a peak in the holdup curve may appear, as obtained by Al-Oufi (Al-Oufi et al, 2010, 2011, Schumpe and Grund (1986), and Zahradnik et al (1997).…”
Section: Bubble Samplingmentioning
confidence: 99%
“…The value depends mainly on the sparger type. Single and multiple nozzles or perforated plate spargers with a hole diameter greater than 1 mm ("coarse" spargers) usually lead to an early regime transition, whereas "fine" spargers such as porous plates (Al-Oufi et al, 2010, 2011 or needles (Mudde et al, 2009) can maintain a stable homogeneous regime at higher gas flowrates (i.e., Mudde et al (2009) reported a homogeneous regime up to a holdup equal to 0.55). The sparger considered in this study is of the "coarse" type, and the values of U trans agree with the data and observations presented in the literature (i.e., the study of Dargar and Macchi (2006) and Rollbusch et al (2015a)).…”
Section: Flow Regime Transitionmentioning
confidence: 99%
“…Experiments were conducted in both the OTBC and AGBC and apart from the addition of various alcohols, the experimental conditions and column specifications are described by Al-oufi et al (2010). The liquid phase used in the experiments consisted of tap water to which ethanol and isopropanol were added in various concentrations.…”
Section: Bubble Columnsmentioning
confidence: 99%
“…Figure 2 illustrates the design and geometry of the four-point probe. In principle, the it operates in a similar way to the two-point probe described in Al-Oufi et al (2010).…”
Section: Probe Design and Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation